PENGELOLAAN BADAN USAHA MILIK DESA (BUM DESA) DI MASA PANDEMI COVID-19 - Aryo Sosiawan (Jurnal Pallangga Praja (JPP), 2022)
Coronavirus disease 2019 (COVID-19) pandemic period is a good momentum for Village Owned Enterprises(BUM Desa) to reorganize their orientation. Not only as a business unit that only pursues economic benefits,but also carries out social functions by playing a more role in social safety nets for the community. In addition,this period is also an important momentum to improve themselves in order to be able to face the complexproblems faced by BUM Desa due to the COVID-19 pandemic. The economic problems faced by both BUMDesa and the community are increasingly complex due to the COVID-19 pandemic. These problems includethe decline in the village economy due to the difficulties experienced by farmers to market their products,the decline in MSMEs, a decrease in people’s purchasing power, and an increase in the economic burdenof the village due to the large number of homecomers returning to the village with problems due to workin the city. This study uses qualitative research conducted through librarians to compare the managementof BUM Desa in various regions. Results of research and management of BUM Desa Overall from variousregions in Indonesia that managing BUM Desa starts with planning, to monitoring the BUM Desa sothat they continue to run as regulated in the regulations and based on the articles of association that havebeen set. And there are also ways to open businesses such as Livestock, LPG gas sales and granulatedsugar distributors and the management of BUM Desa can be done by implementing digitalization so thatmanagement can run more optimally